Nuclear energy an introduction to the concepts, systems, and applications of nuclear processes - Murray, Raymond L., 1920-2011 (Butterworth-Heinemann/Elsevier, 2009)
Nuclear Energy is one of the most popular texts ever published on basic nuclear physics, systems, and applications of nuclear energy. This newest edition continues the tradition of offering a holistic treatment of everything the undergraduate engineering student needs to know in a clear and accessible way. Presented is a comprehensive overview of radioactivity, radiation protection, nuclear reactors, waste disposal, and nuclear medicine. . New coverage on nuclear safety concerns following 9/11, including radiation and terrorism, nuclear plant security, and use of nuclear techniques to detect weapons materials. New facts on nuclear waste management, including the Yucca Mountain repository. New developments in the use of nuclear-powered systems for generating cheap and abundant hydrogen from water using nuclear technology. New information on prospects for new nuclear power reactors and their applications for electricity and desalination. New end-of-chapter Exercises and Answers, lists of Internet resources, and updated references. New instructor web site including Solutions to Exercises and PowerPoint slides. New student web site containing computer programs for use with Computer Exercises.